The Fundación para el Desarrollo de la Región Centro Occidental de Venezuela (Fudeco) : a successful regional development experience (Mayéutica Revista Científica de Humanidades y Artes, 2026)
After 47 years of operation, the Decreto No 8.800 con Rango, Valor y Fuerza de Ley, Presidencia de la República, orders the dissolution and liquidation of the Fundación para el Desarrollo de la Región Centro Occidental,Fudeco.The role he played in the development of the centralwestern region of the country was important, as he contributed to the knowledge of successful experiences in public management and is a reference for scholars of public administration and for those who are venturing into this area. In this document, we attempt to cover the relevant aspects of how the local initiative for its creation and development came about, the working relationship with the various sectors of regional life, its ability to adapt to the changing needs of the region and the country, and its ability to creatively address situations of different natures. On the other hand, it is important to highlight the ethical principles that underpinned the operation that made this atypical institution possible, with successful results.
Keywords: decentralization; development; regionalization; Fudeco; Venezuela